ENHANCING STUDENTS’ WRITING SKILLS THROUGH EFFECTIVE STRATEGIES AND ACADEMIC PRACTICES - Durdona Khamidova; Sevara Tuxmurodova (Bright Mind Publishing, 2025)
Writing is a crucial skill that plays a fundamental role in students’ academic success and future careers. However, many students struggle with writing due to a lack of practice, poor understanding of academic writing principles, and limited feedback. This paper explores effective methods for improving students' writing quality, focusing on structured practice, peer review, and technological tools. The study analyzes existing research and presents strategies that have been proven to enhance writing proficiency. By examining the impact of structured writing exercises and feedback-based improvement, this paper aims to provide practical recommendations for both students and educators.
Keywords: Academic Writing, Writing Skills, Students' Writing Improvement, Writing Strategies, Writing Feedback, Higher Education, Writing Proficiency.